Timber Constructions in Existing Contexts - Krötsch, Stefan, ....-; Stieglmeier, Manfred, ....-; Engel, Thomas, ....- (Munich : Detail Architecture GmbH, 2025)
Timber is an extremely versatile building material that has enjoyed increasing popularity in architecture over many years. Almost any building task can be accomplished with the material by the skilled use of different types of wood and the appropriate methods of construction. Timber is particulary suitable for building in existing stock because it is relatively lightweight and can be successfully prefabricated. Thus even structurally complex vertical extensions to buildings can be erected rapidly on site, which means it is also economically attractive. Moreover, timber also offers impressive solutions for facade refurbishments and horizontal building extensions. Inherently sustainable, timber scores well in life cycle assessments and its structures involve simple connections that are easily dismantled. As a publication in the Detail Practice series, "Timber Constructions in Existing Contexts" provide architects with the specialist knowledge necessary to competently overcome all the challenges of their next refurbishment project. By means of completed practical examples, the book comprehensively illustrates the design and structural engineering possibilities of timber as a construction material for facade modernizations or adding extra storeys and extensions to existing buildings.
Keywords: Houtconstructie -- architectuur